Mommy Bloggers as Rebels and Community Builders: A Generic Description - Petersen, Emily January (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
One site of female activism is mommy blogs, an emerging form of communication in which women can address the constraints and affordances of motherhood. However, female bloggers often face a lack of legitimacy. Generic criticism is one way to recognize female bloggers and address concerns of claiming “professionalism.” Viewing mommy bloggers as a genre reveals substantive and stylistic features that work toward organizing principles, which allow us to see mommy bloggers as a justifiable influence in our culture and in professional communication. This article specifically examines the genre of mommy blogging through the characteristics of the top ten mommy blogs in 2012. These characteristics reveal the two organizing principles of rebellion and community, which are rhetorical choices meant to strengthen the network of bloggers and to extend support to the audience. Mommy blogs offer support, particularly emotional, based on generic constraints in the mothering experience, take into account the context of a situation, act as a community to address the guilt and ambivalence in motherhood, and serve as reports of work, validating the home as a workplace and women’s issues as worthy of discussion and organization. Mommy bloggers engage in feminine rhetoric, finding similarities and engaging in a community-level consciousness raising.